Hubungan Paparan Rokok, Riwayat BCG, dan Riwayat Kontak TB dengan Insidens TB Paru pada Wanita Usia Subur - Mery Andani; Asrul Abdul Azis; Widyaningrum Widyaningrum; Muhsin Mahfudz; Nadyah Haruna (Rumah Sakit Ibnu Sina, Makassar, 2025)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (Mtb), affecting people of all ages globally. In Indonesia, the TB incidence in 2021 was 354 per 100,000 population, with an estimated mortality rate of 52 per 100,000. In South Sulawesi, TB cases rose to 68.8% in 2022 from a 48.3% case detection rate in 2021. This study aimed to assess the association between smoking exposure, BCG vaccination history, and TB contact history with pulmonary TB incidence among women of reproductive age at BBKPM Makassar in 2023. Using a cross-sectional quantitative approach, 354 samples were selected from 3,063 TB cases through purposive sampling. Data were collected from medical records of women aged 15–45 years with new pulmonary TB diagnoses and complete documentation. Chi-square analysis showed significant associations for smoking (p = 0.037), BCG history (p = 0.034), and TB contact (p = 0.004). The study concludes that these factors are significantly related to pulmonary TB in reproductive-age women.